"Yes, the guys can do it!" - Storm, Palle (Teorija in praksa, 2019)
Canada and Sweden are seeing growing numbers of migrant male care workers in long-term care settings, yet research exploring their everyday experiences within this context is scarce. We draw on interview data of migrant men to compare how they come to be in nursing home care work, negotiate their social role, and reconcile and challenge norms about masculinity. The study finds that migrant men work to find a balance and manage tensions related to working in a womencoded field. They attempt to maintain their masculinity without losing their caring approach in both their work and social interactions.
Keywords: Caregivers; Družbena interakcija; Družbena vloga; imigranti; Immigrants; Masculinity; Moškost; Negovalci; negovalni domovi; Priseljenci; skrbstveno delo; Social interaction; Social role